Frequent Causes of Occupational Accidents in Colombia's Footwear Sector 2010-2024: A Literature Review. - Zuluaga Arce, Jhon Alexander
Objetive: To identify the most frequent causes of occupational accidents in Colombia's footwear sector during the 2010-2024 period through a literature review. Materials and Methods: A systematic review was conducted following the PRISMA protocol. The bibliographic search was performed in PubMed, Scopus, Google Scholar, SciELO databases and Colombian institutional repositories. Inclusion criteria included studies published between 2010-2024, in Spanish and English, related to occupational accidents, occupational risk factors and safety management systems in the Colombian footwear industry. Initially, 156 records were identified, of which 35 studies met the established criteria and were thoroughly analyzed. Results: Risk factors were classified into seven categories: ergonomic (88.6% of studies), chemical (77.1%), mechanical (74.3%), physical (54.3%), locative (57.1%), psychosocial (48.6%) and biological (22.9%). Ergonomic risks showed prevalence of musculoskeletal disorders between 52.9% and 87.1%, with low back pain being the most frequent (25.1%). Exposure to neurotoxic chemical substances such as toluene, hexane and ethyl acetate affects 100% of workers in assembly areas. Mechanical accidents represent 22% from impacts and 18% from cuts. Deficient implementation of the Occupational Health and Safety Management System (SG-SST) was identified, with only 40% of companies executing effective preventive programs. Conclusions: Accident rates in the Colombian footwear sector have multifactorial origins, with predominance of ergonomic, chemical and mechanical risks. Micro and small enterprises face economic, technical and organizational limitations that hinder SG-SST implementation. Contextualized mitigation strategies are required including substitution of toxic substances, participatory ergonomics, ventilation improvement, appropriate personal protective equipment provision and strengthening of preventive culture.